Response of Soil Respiration to Grazing in an Alpine Meadow at Three Elevations in Tibet. (24th March 2014) - Fu, Gang; Zhang, Xianzhou; Yu, Chengqun; Shi, Peili; Zhou, Yuting; Li, Yunlong; Yang, Pengwan; Shen, Zhenxi
Abstract : Alpine meadows are one major type of pastureland on the Tibetan Plateau. However, few studies have evaluated the response of soil respiration (R s ) to grazing along an elevation gradient in an alpine meadow on the Tibetan Plateau. Here three fenced enclosures were established in an alpine meadow at three elevations (i.e., 4313 m, 4513 m, and 4693 m) in July 2008. We measured R s inside and outside the three fenced enclosures in July–September, 2010-2011. Topsoil (0–20 cm) samples were gathered in July, August, and September, 2011. There were no significant differences for R s, dissolved organic C (DOC), and belowground root biomass (BGB) between the grazed and ungrazed soils. Soil respiration was positively correlated with soil organic C (SOC), microbial biomass (MBC), DOC, and BGB. In addition, both R s and BGB increased with total N (TN), the ratio of SOC to TN, ammonium N (NH 4 + -N), and the ratio of NH 4 + -N to nitrate N. Our findings suggested that the negligible response of R s to grazing could be directly attributed to that of respiration substrate and that soil N may indirectly affect R s by its effect on BGB.